Clinical outcome of stereotactic body radiotherapy for lung-only oligometastatic head and neck squamous cell carcinoma: Is the deferral of systemic therapy a potential goal?. (June 2019) - Bonomo, Pierluigi; Greto, Daniela; Desideri, Isacco; Loi, Mauro; Di Cataldo, Vanessa; Orlandi, Ester; Iacovelli, Nicola Alessandro; Becherini, Carlotta; Visani, Luca; Salvestrini, Viola; Mariotti, Matteo; Livi, Lorenzo
Highlights: Oligometastatic head and neck squamous cell carcinoma is a rare entity. For lung oligometastases few data are available on stereotactic body radiotherapy. Out of 27 patients, an objective response rate of 75% was achieved. In selected patients, a deferral of systemic therapy may be obtained. Abstract: Objectives: Oligometastatic head and neck squamous cell carcinoma (HNSCC) is a rare entity with no evidence-based treatment recommendations available to support the use of local ablative therapies. The aim of our study was to report on the clinical benefit of stereotactic body radiotherapy (SBRT) for patients with lung-only oligometastases, defined by the presence of 1 to 5 pulmonary lesions. Material and Methods: SBRT was applied in case of single lesions deemed amenable to local treatment only ("de novo" pattern) or after first line chemotherapy at time of disease oligoprogression ("induced" pattern). To assess the potential deferral of systemic therapy in both time points, we analyzed time to progression (TTP) defined as the time from the last day of SBRT to disease progression or death from any cause. Cox regression analysis was performed to identify predictive factors of better outcome. Results: Twenty-seven patients were retrospectively evaluated. The majority (81.5%) had HPV negative disease and a "de novo" oligometastatic pattern (78.6%). The median maximum lesion diameter and target size were 1.5 cm and 22.7 cc, respectively. At a median follow-up of 22 months (range 6–73), the median TTP was 10 months (95% CI: 9.5–21.1), with 1- and 2-year rates of 56.2% and 35%, respectively. The objective response rate at 3 months after SBRT was 75%. At multivariate analysis baseline T3/T4 stage had a HR for worse outcome of 5.38 (p = 0.033). Acute toxicity was minimal (G1/G2 of 14.8%). Conclusion: In properly selected oligometastatic patients, SBRT has potential for sustained deferral of systemic treatment.